2014
DOI: 10.1111/jcpe.12263
|View full text |Cite
|
Sign up to set email alerts
|

The periodontal health component of the Renal Impairment In Secondary Care (RIISC) cohort study: a description of the rationale, methodology and initial baseline results

Abstract: The prevalence and severity of chronic periodontitis in this cohort of CKD patients is markedly higher than a geographically matched control population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
(38 reference statements)
1
36
0
Order By: Relevance
“…Moving beyond the mouth, periodontitis is significantly and independently associated with most chronic inflammatory diseases of ageing, including atherogenic cardiovascular disease, 8 type 2 diabetes, 9 rheumatoid arthritis, 10 chronic kidney disease, 11 obesity, and chronic obstructive pulmonary disease. 12 This is unsurprising given that these conditions all have complex causes and are characterised by chronic inflammation.…”
mentioning
confidence: 99%
“…Moving beyond the mouth, periodontitis is significantly and independently associated with most chronic inflammatory diseases of ageing, including atherogenic cardiovascular disease, 8 type 2 diabetes, 9 rheumatoid arthritis, 10 chronic kidney disease, 11 obesity, and chronic obstructive pulmonary disease. 12 This is unsurprising given that these conditions all have complex causes and are characterised by chronic inflammation.…”
mentioning
confidence: 99%
“…Individuals undergoing dialysis typically have very poor oral health, [136][137][138][139][140][141][142] and for those with long-term hemodialysis, periodontitis is associated with an increased mortality. 137,140,143 One study reported a higher periodontitis risk for older Japanese women with lower cystatin C-based estimated glomerular filtration rate (eGFR).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…53 Among the rural school children between 5 to 15 years, the prevalence of dental caries, plaque, gingival bleeding and bleeding on probing was 69.6%, 91.6%, 66.8 % and 64% respectively. 54 The Link between PD and CAD Periodontitis has been found to be associated with a number of systemic diseases and conditions, including stroke, 55 peripheral arterial disease, 56 type 2 diabetes, 57 rheumatoid arthritis, 58 chronic kidney disease, 59 and chronic obstructive pulmonary disease, 60 Alzheimer's disease, 61 cancers, 62 anaemia, 63 and low-birth weight baby. [64][65] Currently, however, there is a lack of consensus among experts on the nature of these associations and confusion among health care providers and the public on how to interpret this rapidly growing body of science.…”
Section: (Figure 1)mentioning
confidence: 99%